FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PARTISIPASI PETANI DALAM KEGIATAN UNIT PENGOLAH PUPUK ORGANIK (UPPO) DI KABUPATEN KARANGANYAR - Oky Dea Novianti; Dwiningtyas Padmaningrum; Agung Wibowo (AGRITEXTS: Journal of Agricultural Extension, 2020)
:  Farmers’ participation  shows  farmers’ involvement  and  partnership  in  agriculturewhich  include activities of planning, implementing, and utilizing the results of a development program done by local communities. Objectivesof this research were analysing: (1) farmers’ participation in program of Organic Fertilizer Processor Unit or Unit Pengolah Pupuk Organik (UPPO); (2) age, individual’s experience, non-formal education, information access, and farmers’ risk taking in UPPO; and (3) correlation between age, individual’s experience, non-formal education, information access, and farmers’risk taking with participation in UPPO. Basic method of the research was quantitative method with survey technique. Area determination was intentionally decided, the areas that ran UPPO in six villages from five sub-districts, consisting of Pereng and Pendem Villages (Mojogedang Sub-district); Seloromo Village (Jenawi Sub-district), Ngeblak Village (Tawangmangu Sub-district); Kerjo Village (Kerjo Sub- district); Ngadiluwih Village (Matesih Sub-district) in Karanganyar Regency. The sampling technique used proportional random sampling that involved sixty respondents. The analysis data used correlation test of Rank Spearman (r ) with program of IBM SPSS 22.0.  The research result showed that: (1) farmers’ participation in UPPO were included as high category. (2) age included as productive category, individual’s experience included as high category, non-formal education as high category, information access in low category, risk taking included as prepared category. (3) there was significant correlation between individual’s experience, information access, and taking farmers’ risk with farmers’ participation in UPPO, however there was not significant correlation between farmers’age and non-formal education with farmers’participation in UPPO.